2018
DOI: 10.1017/cri.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Associations, Support Group Interventions and Countering Violent Extremism: An Important Step Forward in Combating Violent Radicalization

Abstract: This article offers an introduction for constructing family self-help groups or parent associations in the field of countering violent extremism (CVE) and deradicalization. These support group interventions are an essential addition to recently developed family counseling CVE programs, which have been created in multiple countries since 2012. Based on interviews with parents of deceased foreign terrorist fighters, this article was able to identify the most pressing practical needs of parents and to suggest spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Specifically, it would be expected that these individuals in our sample were exposed to religious beliefs and interpretations amongst family members, and extended family members, which may have exacerbated and reinforced certain opinions and interpretations of religious doctrines and obligations (jihad) or, on the other hand, failed to challenge their emerging ideology. Family members have been identified as particularly applicable to the radicalisation and de-radicalisation process (Harris- Horgan, 2014;Koehler & Ehrt, 2018). Another observation to make is that despite their age, just over onethird of the subjects were married (all Muslim) and that within this context, female partners appeared to play a role in the radicalisation process.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it would be expected that these individuals in our sample were exposed to religious beliefs and interpretations amongst family members, and extended family members, which may have exacerbated and reinforced certain opinions and interpretations of religious doctrines and obligations (jihad) or, on the other hand, failed to challenge their emerging ideology. Family members have been identified as particularly applicable to the radicalisation and de-radicalisation process (Harris- Horgan, 2014;Koehler & Ehrt, 2018). Another observation to make is that despite their age, just over onethird of the subjects were married (all Muslim) and that within this context, female partners appeared to play a role in the radicalisation process.…”
Section: Discussionmentioning
confidence: 99%
“…Through qualitative interviews with mothers who had lost their offspring as foreign fighters, and from a case study of the network "Mothers for Life", Koehler and Ehrt (2018) revealed that families suffer shock, loneliness and trauma after being notified of their child's death. Acquiring adequate professional care, such as trauma therapy, in the aftermath of a child's death is important.…”
Section: Resultsmentioning
confidence: 99%
“…Acquiring adequate professional care, such as trauma therapy, in the aftermath of a child's death is important. The authors suggest that networks, such as "Mothers for Life", may be strengthened by having a strong connection to authorities, which may provide easier access to resources and support parents of potentially radicalising individuals (Koehler & Ehrt, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le famiglie sono sempre più considerate un obiettivo prioritario per la prevenzione da parte di responsabili politici e professionisti nel campo del P/CVE (Koehler, 2015;Koehler, Ehrt, 2018), così come in passato le famiglie sono state oggetto di attenzione, in vista delle "sfide di inclusione" delle nuove generazioni immigrate (Biagioli, 2017). Che si tratti di aumentare la consapevolezza generale sulla radicalizzazione che rafforza la resilienza familiare (Serbati, Milani, 2012), o di consigliare i genitori che possono affrontare un dibattito con i propri figli, le iniziative di P/CVE orientate alla famiglia sono fiorite soprattutto negli ultimi 10 anni.…”
Section: La Famiglia Radicalizzazione Diretta E Indiretta Nei Contesti Dell'educazione Fondamentaleunclassified